Intercomparison of Surface Currents Obtained Using SCHISM and the HF Radar Data in Galveston Bay and Sabine Lake, Texas - Cletus O. Ogbodo; Rosa M. Fitzgerald; Christopher Fuller; Jungwoo Lee; Roberto Perea; Javier Polanco-Gonzalez (Journal of Marine Science and Engineering)
This study provides a comprehensive analysis and intercomparison of surface currents, for Galveston Bay and Sabine Lake, Texas, obtained from High-Frequency (HF) radars and SCHISM model. We established a methodology based on qualitative and quantitative analyses to compare measured and modeled surface currents. One-month HF radar data, in April 2023, were extracted from the two newly installed HF radar networks comprising two and three HF radar stations at Sabine Lake and Galveston Bay, respectively. The extracted surface current data were compared to corresponding SCHISM-simulated currents to assess the model’s performance in predicting currents. The comparison encompassed qualitative and quantitative assessments by evaluating current vectors and the magnitude of eastward and northward velocity components from both methods. The results showed the ocean current predictive capabilities of SCHISM exemplified by their strong correlations (up to 0.94), high index of agreement (up to 0.95), and low error metrics, during the study period. The disparities in the eastward and northward current measurements across the dates underscore the complex interplay between prevailing winds, bay-ocean interactions, and regional weather patterns. This study sheds light on the intricate dynamics of the surface currents in estuaries and nearshore lakes with the underlying efficacy of both the HF radar and SCHISM surface current determinations. The findings can contribute to advancing the understanding of coastal dynamics and determining the strategies for environmental monitoring and management.